Large-tree removal in a mixed-conifer forest halves productivity and increases white fir - Robert A. York (California Agriculture, 2015)
Removing all large trees without planning to replace them with either planted or naturally regenerated younger trees (i.e., high-grading) is widely thought to have negative consequences on a forest's productivity and species composition, but no previous studies in California had evaluated this assumption. To make such an evaluation, I measured productivity and canopy species composition shifts following the repeated removal of large trees and compared the results with those from two other basic forest harvest methods: thinning from below and single tree selection. Timber productivity was substantially lower with large-tree removal (0.65 thousand board feet per acre per year) than with the other methods (averaging 1.33 thousand board feet per acre per year), which included the no-harvest control, where yield was zero. Large-tree removal also resulted in more species change, with white fir increasing in the canopy and ponderosa pine decreasing.